USUL FIKIH DAN UPAYA REORIENTASI FIKIH INDONESIA - Munawir Haris (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2018)
In classical fiqh which is based on the classic Proposal of Jurisprudence, it is often considered outdated and has no effectiveness in dealing with new problems. This paper tries to provide a description of substantive clarification between sharia and fiqh, which is the area of proposal (sharia) and which branch area (fiqh ) Then the discussion continued with its urgency through a hermeneutic approach in carrying out Indonesian local jurisprudence. The Qur'anic texts are fixed, God's laws also do not change and do not change. He never subsided from time to time and from society to other communities. Therefore, changes and changes are only about efforts to adjust and apply the laws of God to the conditions of society and the situation of the times. In other words, fiqh is essentially the result of efforts to harmonize the Shari'a with the conditions of the society and its era. Especially in the Indonesian context, fiqh must also be adapted to the socio-cultural conditions of the Indonesian people known as Indonesian Islamic Jurisprudence or Nusantara Islamic Jurisprudence